Esophagus and Its Function Related to Gastro-esophageal Reflux - Badriul Hegar; Aldo Reynaldo; Yvan Vandenplas (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2012)
ABSTRACTThe main function of the esophagus is to transport food from the mouth into stomach. Anatomical structures, innervations and blood supplies are needed in order to transport the food into stomach. Mastication stimulates the parasympathetic nerves that regulate salivary, gastric and pancreatic secretion. Saliva secretion stimulates swallowing and increases primary esophageal peristalsis, helps in clearing the esophagus from refluxed material. Swallowing induces peristaltic of esophagus that propulses a solid bolus down the esophagus into the stomach.      Innervations are important for esophagus to do its function. One of the most important is coordination between the various reflexes. Delayed clearance of acid from the esophageal and decreased pressure of the lower sphincter esophagus (LES) are the major mechanisms involved in the development of esophagitis. The resistance of the mucosa to the noxious effect of the refluxed material (acid, pepsin, chymotrypsin and trypsin, bile, etc.) is different from person to person. The LES pressure is a defense mechanisms to prevent gastro-esophageal reflux disease (GERD). The LES pressure decreases postprandially. The frequency of postprandinal GER is related to the meal size. Gastric bolus feeding is related to greater intragastric pressure causes more of transient LES relaxations. Osmolality and volume of the feeding slow gastric emptying and incrase postprandial GER. The occurrence of GERD is associated with whether or not the preventive factors are functioning. Other preventive factors for GERD are esophageal peristalsis, secretion and mucosal resistance, gravity and position, the LES tone and angle of his. Patient with GERD should be searched for any disturbances on those factors. Keywords: gastroesophageal reflux diseases, lower esophageal sphincter, esophagitis, peristaltic